On Edge H-Irregularity Strength of Hexagonal and Octagonal Grid Graphs - Muhammad Ibrahim; Ana Gulzar; Muhammad Fazil; Muhammad Naeem Azhar (Journal of Mathematics)
The edge H-irregularity strength, ehsΓ,H, of a graph Γ is the smallest integer k, such that Γ has an H-irregular edge k-labeling. In this study, we compute the exact value of edge H-irregularity strength of hexagonal and octagonal grid graphs.